Baudelaire's world - Lloyd, Rosemary 1949- (Cornell Univ. Press, 2002)
The author offers illuminating readings, critiques of translations, and her own translations of Baudelaire's "world", understood here to include all his works of poetry (both verse and prose), criticism, and correspondence. The study considers the poet's work in its richly textured biographical, historical, and cultural context. At the same time, the author is careful to resist the temptation of facile readings that would unequivocally proclaim a simple inspiration behind a given text.
Keywords: Baudelaire, Charles <1821-1867> - Criticism and interpretation; Baudelaire, Charles <1821-1867> - Critique et interprétation; Baudelaire, Charles <1821-1867> - Translations - History and criticism; Baudelaire, Charles <1821-1867>; Baudelaire, Charles -- 1821-1867; Geschichte 1800-1900; Cultuurgeschiedenis; Frans; Französisch; Kulturgeschichte; Poets, French -- 19th century -- Biography; Biografie